Rethinking Application of Tax Policy on Stainless Food in East Java: A Simulation Analysis - Ahmad Zainuddin; Resti Prastika Destiarni; Ahmad Syariful Jamil (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The Indonesian government has a discourse to implement the tax imposition policy on staple foods during this pandemic. If the policy is implemented, it is feared that it will have a negative impact on the economy, especially in East Java. This study aimed to analyze the East Java economic model and simulate the application of the staple food tax during the COVID-19 pandemic. This study uses an econometric model with a simultaneous equation system using the Two-Stage Least Square (2SLS) method. The analysis results show that the implementation of the basic food tax, either 5 percent or 10 percent, will not have any implications for increasing East Java's GRDP. Moreover, the policy will have implications for the decline of the economy of East Java as a whole. Therefore, the government needs to reconsider the policy of taxing staple foods.